Malignant Peripheral Nerve Sheath Tumor in Frontal Sinus, Orbital Cavity and Ethmoid Cavity - Lee, Jeong Hwan; Kim, Nam Gyun; Lee, Kyung Suk; Kim, Jun Sik (Archives of craniofacial surgery, 2014)
Malignant peripheral nerve sheath tumors are extremely rare soft tissue sarcomas. Among various locations, the trunk and extremities are the most commonly involved sites, with only 15% of such lesions occuring in head and neck region. Here, we report a case of a 74-year-old male who presented with forehead swelling and right eye deviation. Computed tomography images revealed a tumor involving the frontal sinus, ethmoid sinus, and the orbital cavity. The patient underwent a surgical excision of the lesion, which histopathological examination revealed to be a malignant peripheral nerve sheath tumor.